WOMEN IN MEDICINE: STRUCTURAL GENDER INEQUALITIES AND THE GLASS CEILING - Gamze Gürcan; Berfin Nuray Cihangir (Sabuncuoglu Serefeddin Health Sciences, 2026)
Women’s participation in medicine has increased substantially worldwide; however, this growth has not resulted in proportional representation in leadership, academic advancement, or economic equity. This narrative review examines the historical exclusion of women from institutional medicine and the persistence of structural gender inequalities in the profession. Literature published between 2000 and 2025 was identified through PubMed, Scopus, Web of Science, Google Scholar, and reports from the AAMC, WHO, OECD, Eurostat, and TÜİK. A thematic synthesis was conducted focusing on leadership disparities, specialty segregation, work–life conflict, mentorship inequalities, wage gaps, and workplace harassment.Findings indicate that medicine continues to function within gendered organizational structures in which leadership and productivity are frequently defined through masculine norms. Women physicians experience persistent barriers including the “glass ceiling,” limited access to mentorship and sponsorship, discrimination in specialty selection, and the unequal burden of unpaid caregiving responsibilities. Economic disparities extend beyond salary inequities to include motherhood penalties, reduced academic visibility, and disproportionate participation in unpaid institutional labor. Women also remain more vulnerable to workplace harassment, mobbing, burnout, and attrition from academic careers.The review demonstrates that gender inequality in medicine is structurally embedded within institutional cultures and professional hierarchies rather than resulting solely from individual prejudice. Addressing these inequities requires transparent promotion systems, gender-sensitive institutional policies, mentorship and leadership programs, flexible work arrangements, and sustained organizational reform to ensure equitable and sustainable healthcare systems.